Balance sheet shaping through a decision model and funds transfer pricing - Lubińska, Beata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The banking industry is currently facing a number of challenges driven by the regulatory requirements, low or even negative interest rates and margin compression. As a result, active and conscious balance sheet management has increased in importance and banks are required to optimize and allocate resources very precisely to their businesses. There is a clear need for maximization of the assets income, redesign of the funding mix to achieve the lower funding costs and, at the same time, to respect regulatory requirements. This article verifies the hypotheses that the application of the optimization technique improves the management of the banking book in terms of quantifiable impact on a bank’s P&L and that the funds transfer pricing (FTP) process could be used as a mean to achieve the target position of a bank. It proposes a two-step approach to prove the above hypotheses, i.e. the application of the decision model and the FTP process. In addition, the article provides the reader with the main concepts of the FTP process, FTP landscape and details regarding the Balance Sheet shaping
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 140-157
Keywords: funds transfer pricing; decision model; optimization; FTP curve; proces cen transferowych; model decyzyjny; optymalizacja; krzywa cen transferowych